Alunos que ingressaram no ensino superior por ações afirmativas apresentam melhor desempenho? Uma análise empregando a decomposição de Oaxaca para o ENADE 2012 - Gutterres, Rafael dos Santos (2015)
This work seeks to contribute to the debate about the impact of affirmative action has on the higher education system in Brazil. The literature tries to justify affirmative action as a way to reduce inequalities of the past through the promotion of social justice. These measures allow the student to enter in the university, but they may not be sufficient to compensate the family background and educational inequality. For this, we used the performance of finishing students who entered the university through affirmative action (color, income, public school, two criteria and others) through the general test (75% considers the specific component and 25% of general education) of ENADE (Exame Nacional de Desempenho dos Estudantes). The year used for the analysis was 2012, which consists in a sample of 17 courses and over 466 thousand students. The empirical strategy used was the model of ordinary least squares and the method of decomposition of Oaxaca. The OLS allows measuring the effect of affirmative action on student´s performing, controlling the observable characteristics. Oaxaca estimates the differential of notes between the students who entered in Brazilian universities through affirmative action compared to students who entered without the necessity of the measure. The decompose looks for the different grades between observable variables (characteristics of students, educational institutions and the region) and unobservable (effort, dedication, motivation, etc.). The results show that the beneficiaries of the public school students of affirmative action have top notes to non-beneficiary students in all categories of IES analyzed. Color affirmative action beneficiaries and another kind of affirmative action have lower grades in public schools (federal and state) compared to non-beneficiary students, but in private universities the differential note is pro-quota students. Affirmative action of two criteria showed a higher result to beneficiaries’ students in state and private public universities, while in federal public universities was better grades to students not beneficiaries. Finally, beneficiaries’ students affirmative action possessed income lower notes to non-beneficiary students in all categories of analyzed IES. There is evidence showing that for some affirmative action (public school) graduates can compensate for previous inequalities in access to higher education. However, in the case of income measures are insufficient to reduce inequalities arising from their family and school background.